Optical Fiber Sensor Based on Localized Surface Plasmon Resonance Using Silver Nanoparticles Photodeposited on the Optical Fiber End - Ortega-Mendoza, J. Gabriel (Sensors (Basel), 2014)
This paper reports the implementation of an optical fiber sensor to measure the refractive index in aqueous media based on localized surface plasmon resonance (LSPR). We have used a novel technique known as photodeposition to immobilize silver nanoparticles on the optical fiber end. This technique has a simple instrumentation, involves laser light via an optical fiber and silver nanoparticles suspended in an aqueous medium. The optical sensor was assembled using a tungsten lamp as white light, a spectrometer, and an optical fiber with silver nanoparticles. The response of this sensor is such that the LSPR peak wavelength is linearly shifted to longer wavelengths as the refractive index is increased, showing a sensitivity of 67.6 nm/RIU. Experimental results are presented.